Source apportionment and pollution loading in Lake Chini watershed using multivariate statistical analysis - Arafat, Md Yasir (2017)
This study was conducted to assess the surface water quality and sediment contamination status in the Lake Chini and its major tributaries as well as to find out the sources of pollution through different statistical techniques. 15 potentially important locations were selected for water sampling and 10 for sediment, after completion of a survey, whereas 5 geographically important tributaries were selected to understand the pollution loadings they contribute downstream. Water samples were collected six times following standard methods, covering both dry and wet seasons. A total of 16 physicochemical and biological parameters along with 5 heavy metals were measured. Obtained data was compared with NWQS (National Water Quality Standard for Malaysia) and WQI (Water Quality Index) Malaysia as well as multivariate analysis. For sediments, sediment quality guidelines, geo-accumulation index (Igeo), contamination factor (CF) and pollution load index (PLI) were used to evaluate the current data and its status of contamination. From the study, it was found that DO, BOD, COD, total coliform and Fe were higher than the permissible limit in water. Source apportionment study revealed that the major sources of contamination were due to anthropogenic activities especially settlement, mining, agriculture and illegal logging. There was a prominent increasing seasonal trend from dry to wet season for all water quality parameters. Overall water quality at all 15 stations was categorized as class II (suitable for body contact), but having two different contamination status; clean and slightly polluted. Stations at tributaries, draining area of the lake and at the mining area were slightly polluted. Sediments were detected acidic with high organic matter while Fe, Co, Pb and As were higher than the LAL (Low Alert Level). Only Fe value was found beyond normal limit according to contamination factor (CF) while Igeo and all others were within the normal level. Heavy metals pollution status was higher near the tributaries catchment (especially around the mining area) although it was acceptable. Heavy metals contamination had an increasing trend from dry to wet season. However, both water and sediment were contaminated higher in the tributaries channels compared to the lake. The water quality of the lake is class II (88.37) that could be used after conventional treatment and is safe for recreational purpose.